Exploring from creators' perspectives issues and solutions about knowledge, difficulties, and disposal in making smart clothing designs. Issue 1 (2nd January 2018) - Perry, Anna
ABSTRACT: This study, from smart clothing creators' perspectives, empirically investigated issues and solutions about knowledge, difficulties, and disposal in making smart clothing designs. Fifteen creators participated in in-depth interviews. The results indicated that even though participants' educational backgrounds related to smart clothing development, none of the creators had all the necessary knowledge to make smart clothing. To overcome missing knowledge issues, participants have tried various methods: sharing knowledge, self-teaching, learning from existing smart clothing, and working in a team. However, they still meet a lot of difficulties. In addition, lack of knowledge led to limited concerns and solutions for disposal issues. Therefore, a need to cultivate smart clothing creators' knowledge was suggested: educational programmes should be tailored as multidisciplinary courses, including but not limited to material/fibre science, electronic engineering, computer science, apparel design, functional apparel, and eco-design. The findings in this study would contribute to smart clothing development.